Cooperative topology control for low interference in wireless ad hoc networks. (2017) - Wang, Xinglong; Huang, Liusheng; Xu, Hongli
Cooperative communication (CC) can exploit spatial diversity via neighbour's antennas, which may cause serious interference as well. However, previous works rarely consider guaranteeing the interference performance in the cooperative topology control problem for wireless ad hoc networks. In this paper, we first introduce a nodal interference model for the CC scheme. Based on this model, we formalise two critical problems: CTC-MMI which aims to obtain a strongly connected topology with min-max interference, and CTC-MAI which aims to construct a strongly connected topology with min-average interference. Then, we design DBS to solve CTC-MMI optimally. We also propose a distributed algorithm DBCT for CTC-MAI and prove that DBCT can reach the approximate factor of 4. Finally, extensive simulations show that the high efficiency of the proposed algorithms. For example, DBCT can construct the cooperative topology with low-average interference, and reduce the energy consumption by about 30% compared with traditional methods.